EXTRACTION AND PARTIAL PURIFICATION OF ACTINIDIN FROM KIWI FRUITS AND ITS EFFECT ON AGED CHICKEN MEAT: EXTRACTION AND PARTIAL PURIFICATION OF ACTINIDIN FROM KIWI FRUITS AND ITS EFFECT ON AGED CHICKEN MEAT (Iraqi Journal of Market Research and Consumer Protection, 2025)
The aim of this study was to extract the enzyme actinidin from kiwi fruits and purify it partially and determine the pH and the optimum temperature for the effectiveness and stability of the enzyme. Three concentrations of the purified enzyme were used for treatment of aged poultry meat for a period of 2, 4 and 6 h for the purpose of softening it. Some variables used as indicators of oxidation were monitored. The results showed that the crude enzyme had activity of 23 units/ml and specific activity of 19.65 units/mg, and the purification steps resulted in obtaining the enzyme with specific activity of 52.80. The results indicated that the optimal pH for enzyme activity and stability was 7, and the optimum temperature for enzyme activity was 40°C, and the enzyme retained its activity in the range of 20-60 °C. Treating aged chicken breast meat with enzyme led to a significant decrease in peroxide value with increasing enzyme concentration, and it increased with incubation period. The value of total volatile nitrogen was at the lowest value in the control treatment (5.44%) and increased with increasing enzyme concentration and incubation period. The values ​​of Thio barbituric acid showed a significant increase in the control treatment and reached its highest value in the longest incubation period, and actinidin enzyme decreased the values ​​of Thio barbituric acid at all concentrations used. The values ​​of free fatty acids decreased in the enzyme-containing treatments, compared to the control, which gave the highest value (0.68 for an 8-h incubation period).